Time-convenient deformation of musculoskeletal system - Kellnhofer, Petr; Kohout, Josef (Proceedings of the Conference Algoritmy, 2015)
The musculoskeletal modelling and simulation is an essential step in the process of looking for an optimal strategy to provide patients suering from various musculoskeletal disorders, such as osteoporosis, with better health care. In our previous work, we proposed a deformation method suitable for clinical practise that deforms each muscle represented by a surface mesh according to assigned skeleton action lines and preserves its inner volume at the same time. It is built on combination of linear constraints for surface description together with relation of surface to control skeleton and non-linear constraint of volume preservation. It uses Gauss-Newton based iterative solver to find energy minimum fullling these conditions. It gains extra performance from exploiting the coarse outer hull for potentially slow and numerically unstable calculations. It achieves excellent ratios of volume preservation and maintains reasonable times in hundreds of milliseconds for our typical meshes, but since each mesh is deformed independently to others, it is unable to provide deformation of multiple interacting meshes without danger of their mutual intersections. This is why a new modication of the method is introduced in this paper that alters both constraint formulation and the iterative solver algorithm to x and prevent major intersections between mesh surfaces. It detects and prevents initial intersections in the starting pose of meshes and then prevents new intersections during the solution by constraining the modication step of meshes. It however still considers importance of volume preservation and tries to minimize effect of changes on its maintenance. The method was implemented in C++ language and VTK framework and integrated to our human body framework. The results of application to medical data we use show that despite of a few open issues, the proposed technique has its merit.